2015
DOI: 10.1124/dmd.114.059345
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Metabolites to P450 Inhibition–Based Drug–Drug Interactions: Scholarship from the Drug Metabolism Leadership Group of the Innovation and Quality Consortium Metabolite Group

Abstract: Recent European Medicines Agency (final) and US Food and Drug Administration (draft) drug interaction guidances proposed that human circulating metabolites should be investigated in vitro for their drug-drug interaction (DDI) potential if present at ‡25% of the parent area under the time-concentration curve (AUC) (US Food and Drug Administration) or ‡25% of the parent and ‡10% of the total drug-related AUC (European Medicines Agency). To examine the application of these regulatory recommendations, a group of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 55 publications
0
32
0
Order By: Relevance
“…Such cases are relatively infrequent (Yeung et al, 2011;Callegari et al, 2013;Yu and Tweedie, 2013;Yu et al, 2015). However in one instance the inhibition of cerivastatin clearance (mediated by CYP2C8 and OATP1B1) by the glucuronide metabolite of gemfibrozil led to tragic consequences (Staffa et al, 2002;Shitara et al, 2004).…”
Section: Dmd/2017/079848mentioning
confidence: 99%
“…Such cases are relatively infrequent (Yeung et al, 2011;Callegari et al, 2013;Yu and Tweedie, 2013;Yu et al, 2015). However in one instance the inhibition of cerivastatin clearance (mediated by CYP2C8 and OATP1B1) by the glucuronide metabolite of gemfibrozil led to tragic consequences (Staffa et al, 2002;Shitara et al, 2004).…”
Section: Dmd/2017/079848mentioning
confidence: 99%
“…Recently, a group of scientists, under the auspices of the Drug Metabolism Leadership Group of the Innovation and Quality Consortium, conducted an evaluation of having a metabolite as the sole contributor to P450 inhibition-based DDIs. After a thorough review of the literature and analysis of frequently prescribed drugs, the group concluded that the risk of P450 inhibition caused by a metabolite alone is low (Yu et al, 2015). In the current study, we highlight the role of AO in the formation of the hydroxyl metabolite of decernotinib [(R)-2-((2-(1H-pyrrolo [2,3-b]pyridin-3-yl)pyrimidin-4-yl)amino)-2-methyl-N-(2,2,2-trifluoroethyl)butanamide (VX-509)], which may be the major contributor involved in a TDI-based DDI.…”
Section: )mentioning
confidence: 99%
“…AMIO, itself, appears to be a fairly weak in vitro inhibitor of these enzymes (Kobayashi et al, 1998;Ohyama et al, 2000), which raises the possibility that inhibitory metabolites play a more direct role than the parent drug. In fact, a recent literature review identified AMIO as one of only five out of 137 total pharmaceuticals to cause a metabolism-dependent clinical DDI judged to be due entirely to an inhibitory metabolite(s), with little to no contribution of the parent drug (Yu et al, 2015). Therefore, a more complete analysis of AMIO-P450 inhibition should provide a useful case study in helping to determine which future drugs are more at risk of a metabolism-dependent DDI caused by inhibitory metabolites.…”
Section: Introductionmentioning
confidence: 99%